Analisis Kualitas Pelayanan Publik dengan Metode Integrasi Servqual dan Diagram Kartesius - Wahju Wibowo; Imam Nuryanto (STEKOM PRESS, 2022)
Measurement of customer satisfaction is something that should be done by a public service organization periodically, improving performance on the right attributes will have a positive impact, namely increasing satisfaction of public service users. This study aims to measure customer satisfaction of public service users by integrating the servqual model and the cartesian diagram model. The analysis tool uses SPSS, with a sample of 121 respondents. The results showed that the quality of public services at the Shipping Polytechnic of North Sulawesi was good, at an average performance score of 8.79 from the rating scale range, and was able to satisfy the expectations of service users. The main dimensions that must be improved immediately are reliability, assurance and tangible. At the attribute of service requirements information, service completion time period information and service supporting infrastructure facilities. With the findings of this study, it is hoped that public services can be improved and the attributes of services that are already good can be maintained.